2010
DOI: 10.1128/iai.01323-09
|View full text |Cite
|
Sign up to set email alerts
|

Intrapulmonary Administration of Leukotriene B4Enhances Pulmonary Host Defense against Pneumococcal Pneumonia

Abstract: Leukotriene B 4 (LTB 4 ) is a potent lipid mediator of inflammation formed by the 5-lipoxygenase (5-LO)-catalyzed oxidation of arachidonic acid. We have previously shown that (i) LTB 4 is generated during infection, (ii) its biosynthesis is essential for optimal antimicrobial host defense, (iii) LT deficiency is associated with clinical states of immunocompromise, and (iv) exogenous LTB 4 augments antimicrobial functions in phagocytes. Here, we sought to determine whether the administration of LTB 4 has therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 51 publications
7
55
0
Order By: Relevance
“…We have previously confirmed the role of NADPH oxidase in LTB 4 -mediated killing of K. pneumoniae as suggested by pharmacologic studies with AMs derived from gp91phox Ϫ/Ϫ mice (14). In addition, LTB 4 can promote NADPH oxidase activation by various mechanisms, including enhancement of phosphorylation and membrane translocation of the NADPH oxidase subunit p47phox (14) and also by enhancing the expression of the gp91phox subunit (80). Interestingly, LTD 4 -induced C. albicans killing was only partially dependent on NADPH oxidase activation.…”
Section: Discussionsupporting
confidence: 76%
“…We have previously confirmed the role of NADPH oxidase in LTB 4 -mediated killing of K. pneumoniae as suggested by pharmacologic studies with AMs derived from gp91phox Ϫ/Ϫ mice (14). In addition, LTB 4 can promote NADPH oxidase activation by various mechanisms, including enhancement of phosphorylation and membrane translocation of the NADPH oxidase subunit p47phox (14) and also by enhancing the expression of the gp91phox subunit (80). Interestingly, LTD 4 -induced C. albicans killing was only partially dependent on NADPH oxidase activation.…”
Section: Discussionsupporting
confidence: 76%
“…Administration of LTB 4 by aerosol augmented nuclear p50 staining in macrophages from both genotypes, restoring the p50 translocation response in 5-LO -/-mice to the level observed in infected WT animals. Consistent with these results, we recently reported that administration of LTB 4 using this protocol also enhances lung bacterial clearance in 5-LO -/-animals (27). Interestingly, we did not observe p50 nuclear translocation in neutrophils from either genotype in the absence or presence of aerosolized LTB 4 (data not shown).…”
Section: Figuresupporting
confidence: 79%
“…pneumoniae infection. S. pneumoniae serotype 3, 6,303 (ATCC) was grown, and mice were infected, as described previously (27).…”
Section: Animals 8-week-old Female 5-lomentioning
confidence: 99%
“…These observations suggest that there is a complex interplay between CC and CXC chemokines. LTB 4 is a known neutrophil chemotactic lipid which can be generated by leukocytes from arachidonic acid (19) and act via G protein-coupled receptors to cause leukocyte accumulation, microbial killing, and generation of proinflammatory mediators (26,36). In an earlier study using the CLP model, it has been shown that MCP-1 inhibition attenuated neutrophil influx via the downregulation of LTB 4 production (37).…”
Section: Discussionmentioning
confidence: 99%